A multidisciplinary team approach to screening, assessment and early intervention for young people with type 1 diabetes and disordered eating behaviour. (July 2021) - Simmons, Anna; McMahon, Lauren; Crosbie, Vivienne; Carlson, Lyndsey
Introduction: Recent NICE guidelines have emphasised the need for diabetes and eating disorder teams to collaborate in order to provide safe and effective treatment for young people with type 1 diabetes and eating disorders. Aim: Our aim was to examine and describe the current treatment journeys for young people under the care of our paediatric diabetes team who presented with eating difficulties and body image concerns. We also sought to increase staff awareness, communication and opportunities for joint working across the diabetes and eating disorders teams. Method: Information regarding the screening, assessment and interventions offered to young people with type 1 diabetes and eating difficulties was collected. A joint training event was developed and attended by healthcare professionals from the diabetes and eating disorder teams. Results: Information collected regarding patient's treatment journeys was used to inform the multidisciplinary pathway. The joint training event offered the opportunity for shared learning, and identification of areas for service improvement.